SPE Western Regional Meeting 2016
DOI: 10.2118/180372-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling of Clay Swelling in Hydraulic Fractures Network

Abstract: Hydraulic fracturing is the most effective technique used in the oil industry for economical production of hydrocarbon from very low permeability reservoirs. Recent experimental studies have indicated a change in hydraulic fractures (HF) conductivity as the result of the interactions between fracturing fluid and shale matrix. Clay swelling is one of the well-known undesirable interactions of this kind. If clay swelling occurs on the surface of hydraulic fractures, it can cause a major damage to the overall per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Swell. Experimental and simulation works have shown that clay minerals could expand in volume up to 20 times through adsorption of water [27], which lead to fracture permeability decrease 10% to 90% based on different kinds of clay minerals and clay content in shale samples [28]. Hence, the swelling effect is considered when analyzing fracture aperture evolution in our experiments.…”
Section: Effective Hydraulic Aperture Decrease Induced By Claymentioning
confidence: 98%
“…Swell. Experimental and simulation works have shown that clay minerals could expand in volume up to 20 times through adsorption of water [27], which lead to fracture permeability decrease 10% to 90% based on different kinds of clay minerals and clay content in shale samples [28]. Hence, the swelling effect is considered when analyzing fracture aperture evolution in our experiments.…”
Section: Effective Hydraulic Aperture Decrease Induced By Claymentioning
confidence: 98%
“…caused the expansion of a double diffusive layer of clay minerals [32]. Consequently, the clay swelling may lead to the increase of clay mineral content of carbonate-poor and carbonate-rich shale.…”
Section: Geofluidsmentioning
confidence: 99%